Stability analysis of underground oil storage caverns by an integrated numerical and microseismic monitoring approach. (April 2016) - Ma, K.; Tang, C.A.; Wang, L.X.; Tang, D.H.; Zhuang, D.Y.; Zhang, Q.B.; Zhao, J.
Abstract: Underground storage in unlined caverns is of great significance for storing energy resources. Construction of underground storage caverns is an extremely complex process, involving extensive multi-bench excavation and strong unloading. Excavation-induced damage of surrounding rock masses may lead to instability of underground storage caverns. The aim of this paper is to put forward a method by integrating numerical simulation and microseismic monitoring for evaluation of cavern stability. A novel numerical method called Continuous–Discontinuous Element Method (CDEM) is applied to simulate micro-cracks under excavation-induced unloading conditions. Meanwhile, a microseismic (MS) monitoring system is employed to monitor real-time MS events during construction of storage caverns. Numerical results are validated using the monitoring data from the MS monitoring system. The integrated method is proved to be successful in capturing micro-cracks in underground storage caverns. Local instability, potential unstable zones and micro-crack evolution are analyzed, and cracking mechanisms are also discussed.